Alexithymia modulates the experience of the rubber hand illusion - Grynberg, Delphine; Pollatos, Olga (Frontiers in Human Neuroscience, 2015)
Alexithymia is associated with lower awareness of emotional and non-emotional internal bodily signals. However, evidence suggesting that alexithymia modulates body awareness at an external level is scarce. This study aimed to investigate whether alexithymia is associated with disrupted multisensory integration by using the rubber hand illusion task. Fifty healthy individuals completed the Toronto Alexithymia Scale and underwent the rubber hand illusion measure. In this measure, one watches a rubber hand being stroked synchronously or asynchronously with one’s own hand, which is hidden from view. Compared to the asynchronous stimulation, the synchronous stimulation results in the illusion that the rubber hand and the participant’s hand are closer together than they really are and that the rubber hand belongs to them. Results revealed that higher levels of alexithymia are associated with a lower ownership illusion. In conclusion, our findings demonstrate that high alexithymia scorers integrate two simultaneous sensory and proprioceptive events into a single experience (lower multisensory integration) to a lesser extent than low alexithymia scorers. Higher susceptibility to the illusion in high alexithymia scorers may -indicate that alexithymia is associated with impaired multisensory integration and that this association results from an abnormal focus of one's own body.